Ecological and anthropogenic drivers of rabies exposure in vampire bats: implications for transmission and control - Streicker, Daniel G. (The Royal Society, 2012)
Despite extensive culling of common vampire bats in Latin America, lethal human rabies outbreaks transmitted by this species are increasingly recognized, and livestock rabies occurs with striking frequency. To identify the individual and population-level factors driving rabies virus (RV) transmission in vampire bats, we conducted a longitudinal capture–recapture study in 20 vampire bat colonies spanning four regions of Peru. Serology demonstrated the circulation of RV in vampire bats from all regions in all years. Seroprevalence ranged from 3 to 28 per cent and was highest in juvenile and sub-adult bats. RV exposure was independent of bat colony size, consistent with an absence of population density thresholds for viral invasion and extinction. Culling campaigns implemented during our study failed to reduce seroprevalence and were perhaps counterproductive for disease control owing to the targeted removal of adults, but potentially greater importance of juvenile and sub-adult bats for transmission. These findings provide new insights into the mechanisms of RV maintenance in vampire bats and highlight the need for ecologically informed approaches to rabies prevention in Latin America.